Effect of lecithin on disability and plasma free-choline levels in Friedreich's ataxia. Issue 9 (September 1980) - Chamberlain, S; Robinson, N; Walker, J; Smith, C; Benton, S; Kennard, C; Swash, M; Kilkenny, B; Bradbury, S
Abstract : Four patients with Friedreich's ataxia took part in an open trial, in which they consumed 50-100g/day lecithin granules (containing approximately 22% phosphatidycholine) for 16 weeks, but no improvement resulted. Several unwanted effects including diarrhoea, nausea, depression, "hot flushes" and weakness were experienced. Resting levels of free-choline in plasma were within the range found in 19 normal subjects. Sixteen other patients with Friedreich's ataxia also had normal free-choline levels. Treatment with lecithin significantly increased plasma free-choline levels, but there was a trend for these to fall towards baseline levels, despite continued ingestion of lecithin.